2014
DOI: 10.1016/j.jaapos.2014.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Binocular inhibition in strabismic patients is associated with diminished quality of life

Abstract: Purpose This prospective study aims to characterize the relationship between binocular summation (BiS) and binocular inhibition (BI) on the quality of life (QoL) of adult and pediatric patients with strabismus. Methods A binocular summation score was measured using ETDRS and Sloan low contrast acuity (LCA) protocols at 2.5% and 1.25% contrast. Patients were categorized as having BiS (binocular visual acuity superior than better-eye visual acuity by 5 or more letters), BI (binocular visual acuity worse than b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…In our study, patients who recovered binocular function after surgery had better scores than those without binocular function in both subscales. The above finding is also supported by a previous report that patients without binocular inhibition had better HRQOL than those with inhibition[11]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, patients who recovered binocular function after surgery had better scores than those without binocular function in both subscales. The above finding is also supported by a previous report that patients without binocular inhibition had better HRQOL than those with inhibition[11]. …”
Section: Discussionsupporting
confidence: 87%
“…In patients with strabismus, the factors affecting patient HRQOL are related to strabismus characteristics[911]; demographics[12]; psychosocial parameters, such as mood, depression, and self-esteem; and understanding of strabismus[1315]. HRQOL can be improved after corrective surgery in both the short term (6 weeks to 90 days) and long term (1 year to 18 months),as assessed via the Adult Strabismus-20 (AS-20), the Amblyopia and Strabismus Questionnaire (A&SQ), and other generic questionnaires[1621].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that strabismic patients have subnormal binocular summation, and even binocular inhibition (worse visual function with binocular compared to monocular viewing) and this is associated with diminished quality of life. 19, 20 Our findings suggest that diplopia and other factors affecting vision in strabismic patients may have a greater impact on visual functioning than factors affecting vision in the other ocular diseases studied.…”
Section: Discussionmentioning
confidence: 67%
“…22 Moreover, decreased binocular summation in strabismic patients is associated with worse quality of life, emphasizing the importance of improving binocularity. 29 Our previous studies, however, deliberately excluded patients with strabismic amblyopia because of known impairment by amblyopia of binocular summation, 11, 28 and it is unknown if amblyopia further degrades binocular summation beyond that due to strabismus alone.…”
Section: Introductionmentioning
confidence: 99%